Equitable Maritime Law Policy: A Study of the Blue Constitution and Environmental Fiqh Regarding Land Use Rights in Tangerang, Banten - Dhika Tabrozi; Siti Fatimah; Muhammad Adib Alfarisi; Misbahul Mujib; Ratnasari Fajariya Abidin (UIN Sunan Kalijaga Yogyakarta, 2026)
Environmental issues in Indonesia reveal signs of an ecological crisis that directly impacts humanity as the stewards of the earth. This situation is evident in the state’s failure to uphold ecological justice, as seen in extractivist practices such as the construction of a sea wall in Tangerang–Banten. The case of Building Use Rights (HGB) permits in this marine area indicates a disregard for the state’s constitutional obligation to protect environmental sustainability and potentially deviates from state and religious norms. This study aims to examine the political character of environmental law in the HGB permitting policy for the bamboo seawall in Tangerang–Banten using the “blue constitution” and environmental fiqh as analytical tools. The approach used is socio-normative through content analysis of legislation, Constitutional Court rulings, and environmental fiqh literature. The results of the study indicate that the granting of HGB to private parties in the marine area constitutes a deviation from constitutional norms, as it has the potential to privatize marine space—a practice explicitly rejected in Constitutional Court Ruling No. 3/PUU-VIII/2010. From an environmental fiqh perspective, such actions contradict the prohibition against destruction (ifsād) as stated in QS. al-A‘rāf: 56 and the principles of hifz al-bi’ah. Environmental fiqh in this study does not rely on maslahah mursalah, but rather on maslahah mu‘tabarah, which is reinforced by sharia evidences regarding the obligation to preserve ecosystem sustainability. The integration of the blue constitution concept and environmental fiqh provides an analytical framework for evaluating policies in a more eco-centric manner, viewing the sea not merely as an economic space, but as an ecological entity that possesses the right to protection. The implications of this study underscore the need for a licensing policy design that is more socially and ecologically just and consistent with the constitutional mandate and the principle of hifz al-bi’ah in Islamic law. Persoalan lingkungan hidup di Indonesia menunjukkan gejala krisis ekologis yang berdampak langsung pada kemanusiaan sebagai penjaga bumi. Kondisi tersebut tampak pada absennya negara dalam menjalankan peran menjaga keadilan ekologis, sebagaimana terlihat dalam praktik ekstraktivisme melalui pembangunan pagar laut di Tangerang–Banten. Kasus perizinan Hak Guna Bangunan (HGB) pada wilayah laut tersebut menunjukkan adanya pengabaian terhadap kewajiban konstitusional negara untuk melindungi kelestarian lingkungan serta berpotensi menyimpang dari norma negara dan agama. Penelitian ini bertujuan mengkaji karakter politik hukum lingkungan dalam kebijakan perizinan HGB pagar bambu di Tangerang-Banten dengan menggunakan blue constitution dan fikih lingkungan sebagai alat analisis. Pendekatan yang digunakan adalah sosio-normatif melalui analisis konten terhadap peraturan perundang-undangan, putusan Mahkamah Konstitusi, serta literatur fikih lingkungan. Hasil penelitian menunjukkan bahwa pemberian HGB kepada pihak swasta di wilayah laut merupakan bentuk penyimpangan norma konstitusi, karena berpotensi memprivatisasi ruang laut yang secara tegas ditolak dalam Putusan MK No. 3/PUU-VIII/2010. Dari perspektif fikih lingkungan, tindakan tersebut bertentangan dengan larangan perusakan (ifsād) sebagaimana termaktub dalam QS. al-A‘rāf: 56 dan prinsip-prinsip hifz al-bi’ah. Fikih lingkungan dalam penelitian ini tidak bertumpu pada maslahah mursalah, melainkan pada maslahah mu‘tabarah yang diperkuat oleh dalil-dalil syar‘i mengenai kewajiban menjaga kelestarian ekosistem. Integrasi konsep blue constitution dan fikih lingkungan menyediakan kerangka analitis untuk menilai kebijakan secara lebih ekosentris, memandang laut bukan semata ruang ekonomi, tetapi entitas ekologis yang memiliki hak untuk dilindungi. Implikasi penelitian ini menegaskan perlunya desain kebijakan perizinan yang lebih adil secara sosial-ekologis serta konsisten dengan mandat konstitusi dan prinsip hifz al-bi’ah dalam hukum Islam.